PENGARUH MOTIVASI, DISIPLIN, LINGKUNGAN TERHADAP KINERJA DAN PERAN KEPUASAN KERJA KARYAWAN DI DINAS SOSIAL KOTA SURABAYA - Risanda Regitasari; Tatik Suryani (Jurnal Ilmiah Global Education, 2023)
This study was conducted to obtain empirical evidence of the effect of motivation, discipline, environment on employee performance and job satisfaction at the Surabaya City Social Service. This research uses a quantitative approach. This study uses purposive sampling technique which means sampling techniques for specific purposes oriented to the population and specific objectives. The sample in this study were employees of the Surabaya City Social Service. The data processing analysis tool method in this study uses SEM SmartPLS 3.0. The results of this study are H1 rejected, H2 accepted, H3 accepted, H4 rejected, H5 rejected.